Fanaticism : a political philosophical history - Goldsmith, Zachary Robert (University of Pennsylvania Press, 2022)
"As the post-WWII liberal democratic consensus comes under assault around the globe, this book investigates a timely topic: the re-emergence of fanaticism. Fanaticism: A Philosophical Political History traces the history of the concept from ancient times to our present moment of extremism run amok, offering a novel account of a term that resists easy definition. Drawing on the work of Immanuel Kant, Edmund Burke, and Fyodor Dostoevsky, Zachary R. Goldsmith explores fanaticism's transformation into a political concept around the time of the French Revolution, and in the process, shows us why fanaticism is antidemocratic, illiberal, anti-political, and never necessary"--